2008
DOI: 10.3357/asem.2361.2008
|View full text |Cite
|
Sign up to set email alerts
|

Two Hypoxia Sensor Genes and Their Association with Symptoms of Acute Mountain Sickness in Sherpas

Abstract: These genetic variants of HIF1A and VHL are not associated with AMS symptoms that occur in Sherpas at extremely high altitudes. It seems unlikely that HIF1A and VHL are associated with hypoxic sensing sensitivity in Sherpas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…Second, our controls were recruited from the hospital, so we could not exclude the inherent selection bias for any particular genotype. However, the genotype distributions of the controls in our study were similar to distributions reported to as typical for Asian population in other studies and conformed to Hardy-Weinberg Equilibrium (Droma et al, 2008;Qin et al, 2011). Third, ethnic variation is known to be a major risk for PCa.…”
Section: Discussionsupporting
confidence: 81%
“…Second, our controls were recruited from the hospital, so we could not exclude the inherent selection bias for any particular genotype. However, the genotype distributions of the controls in our study were similar to distributions reported to as typical for Asian population in other studies and conformed to Hardy-Weinberg Equilibrium (Droma et al, 2008;Qin et al, 2011). Third, ethnic variation is known to be a major risk for PCa.…”
Section: Discussionsupporting
confidence: 81%
“…Several groups have reported AMS susceptibility related to SNP variants (Droma et al, 2008), while others have reported no association (Dehnert et al, 2002;Koehle et al, 2006). Therefore, it remains a challenge to determine which genes and genetic determinants are actually involved in the development of AMS.…”
Section: Introductionmentioning
confidence: 96%
“…A large number of candidate genes have been associated with AMS susceptibility, including the angiotensin-converting enzyme (ACE), angiotensin II (Ang II) type 1 receptor, beta-2 adrenergic receptor, bradykinin receptor-B2, heat shock protein 70, endothelial nitric oxide synthase, hypoxia-inducible factor 1 alpha, and vascular endothelial growth factor (Dehnert et al, 2002;Zhou et al, 2005;Koehle et al, 2006;Wang et al, 2007;Droma et al, 2008;Kalson et al, 2009;Buroker et al, 2010;Hennis et al, 2010;Ding et al, 2011). Several groups have reported AMS susceptibility related to SNP variants (Droma et al, 2008), while others have reported no association (Dehnert et al, 2002;Koehle et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…However, their study did not reveal such an association. Maybe another set of genes, or genetic mechanisms determines the susceptibility of individuals to high altitude (Droma et al, 2008). Diet and oral antioxidant supplements may have a role in the body's response to high altitude.…”
Section: High Altitude Related Oxidative Stress and Antioxidant Defenmentioning
confidence: 99%